Update in collecting duct carcinoma: Current aspects of the clinical and molecular characterization of an orphan disease - Suarez, Cristina; Marmolejo, David; Valdivia, Augusto; Morales-Barrera, Rafael; Gonzalez, Macarena; Mateo, Joaquin; Semidey, Maria Eugenia; Lorente, David; Trilla, Enrique; Carles, Joan (Frontiers in Oncology, 2022)
Collecting duct renal cell carcinoma (cdRCC), which until recently was thought to arise from the collecting ducts of Bellini in the renal medulla, is a rare and aggressive type of non-clear renal cell carcinoma (ncRCC), accounting for 1% of all renal tumors and with nearly 50% of patients being diagnosed with Stage IV disease. The median overall survival in this setting is less than 12 months. Several regimens of chemotherapies had been used based on morphologic and cytogenetic similarities with urothelial cell carcinoma described previously, although the prognosis still remains poor. The use of targeted therapies also did not result in favorable outcomes. Recent works using NGS have highlighted genomic alterations in SETD2, CDKN2A, SMARCB1, and NF2. Moreover, transcriptomic studies have confirmed the differences between urothelial carcinoma and cdRCC, the possible true origin of this disease in the distal convoluted tubule (DCT), differentiating from other RCC (e.g., clear cell and papillary) that derive from the proximal convoluted tubule (PCT), and enrichment in immune cells that may harbor insights in novel treatment strategies with immunotherapy and target agents. In this review, we update the current aspects of the clinical, molecular characterization, and new targeted therapeutic options for Collecting duct carcinoma and highlight the future perspectives of treatment in this setting.